2001
DOI: 10.1159/000049167
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide for Cancer of the Liver and Biliary Tree

Abstract: Inoperable liver tumors have an unfavorable natural course despite various therapeutic modalities. Octreotide, a somatostatin analog, has shown considerable antitumor activity on animal models of various hepatic tumors and on isolated cell culture lines. In this paper, a review of the experimental evidence is presented. Moreover clinical papers of case reports of uncontrolled studies of patients are also reviewed. The majority of clinical studies provide evidence of a clinical and biochemical response of liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 76 publications
0
14
1
4
Order By: Relevance
“…9 Different mechanisms of action including stimulation of Kupffer cells and antimitotic effect through inhibition of insulin-like growth factor I and engagement of receptors expressed by tumor cells have been postulated. 10,11 Forty-one percent of HCC express somatostatin receptors according to one study. 12 HCC predominantly expresses somatostatin-receptor subtype 2.…”
Section: H Epatocellular Carcinoma (Hcc) Is Responsiblementioning
confidence: 99%
“…9 Different mechanisms of action including stimulation of Kupffer cells and antimitotic effect through inhibition of insulin-like growth factor I and engagement of receptors expressed by tumor cells have been postulated. 10,11 Forty-one percent of HCC express somatostatin receptors according to one study. 12 HCC predominantly expresses somatostatin-receptor subtype 2.…”
Section: H Epatocellular Carcinoma (Hcc) Is Responsiblementioning
confidence: 99%
“…9 These results suggest that octreotide may indirectly affect tumor growth through inhibition of release of some peptides or growth factors such as insulin, EGF and IGF-1, which promote tumor proliferation. 26 Although octreotide could inhibit the growth of gastric adenocarcinoma, the inhibition rate (60.6%) for gastric xenografts treated by octreotide alone 8 was also much lower than the result of rofecoxib plus octreotide in vivo with the same animal model, drug doses and schedules. Furthermore, the combination therapy potentially promoted the fibrosis of gastric adenocarcinoma in nude mice when compared with the rofecoxib group or control.…”
Section: Discussionmentioning
confidence: 98%
“…OCT is a cyclic octapeptide containing two D-configuration amino acids, with high binding affinity for somatostatin receptor (SSTR) 2 and 5, reduced affinity for SSTR3, and no affinity for SSTR1 and SSTR4 (1). The therapeutic potential of OCT has recently been extended to nonendocrine tumors, particularly primary hepatocelluar carcinoma (HCC) (2). Substantial evidence from experimental studies and clinical trials showed that OCT improved the survival benefits of patients with HCC (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence from experimental studies and clinical trials showed that OCT improved the survival benefits of patients with HCC (3)(4)(5). The antineoplastic effects have been attributed to indirect inhibition of insulinlike growth factor-1 (IGF-1) through downregulation of growth hormone (GH) release, direct inhibition of tumor angiogenesis, antiproliferation of tumor cells, and stimulation of the reticuloendothelial system (RES) by unknown mechanisms (2,6,7).…”
Section: Introductionmentioning
confidence: 99%